2021
DOI: 10.1002/ctm2.577
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein resensitizes tamoxifen‐resistant breast cancer cells by reducing aerobic glycolysis and reversing mitochondrial dysfunction via inhibition of hypoxia‐inducible factor‐1α

Abstract: Drug resistance is a major hurdle for the effectiveness of tamoxifen (TAM) to provide clinical benefit. Therefore, it is essential to identify a sensitizer that could be used to improve TAM efficacy in treating TAM‐resistant breast cancer. Here, we investigated the ability of baicalein to reverse TAM resistance. We found that baicalein increased the efficacy of TAM in inhibiting proliferation and inducing apoptosis of TAM‐resistant cells. It also enhanced the TAM‐induced growth reduction of resistant cells fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…Recent findings by Chen and his colleagues suggested that baicalein significantly enhanced the oral-bioavailability of tamoxifen (TAM). The nuclear translocation and transcriptional activity of hypoxia-inducible factor-1α (HIF-1α) were reduced by baicalein, which contributed to the downregulation of HIF-1α–mediated glycolysis uptake and recovered the number and shape of mitochondria as well as their ability to generate ROS, and thus re-sensitized breast cancer cells to TAM treatment [ 103 ]. As a critical chemotherapeutic agent currently utilized in the treatment of a wide range of cancers, cisplatin exerts its cytotoxic effects in tumor cells primarily through the production of deoxyribonucleic acid-platinum complexes and the subsequent deoxyribonucleic acid damage response [ 104 ].…”
Section: Applications Of Flavonoids In Sr In Reversing Drug-resistanc...mentioning
confidence: 99%
“…Recent findings by Chen and his colleagues suggested that baicalein significantly enhanced the oral-bioavailability of tamoxifen (TAM). The nuclear translocation and transcriptional activity of hypoxia-inducible factor-1α (HIF-1α) were reduced by baicalein, which contributed to the downregulation of HIF-1α–mediated glycolysis uptake and recovered the number and shape of mitochondria as well as their ability to generate ROS, and thus re-sensitized breast cancer cells to TAM treatment [ 103 ]. As a critical chemotherapeutic agent currently utilized in the treatment of a wide range of cancers, cisplatin exerts its cytotoxic effects in tumor cells primarily through the production of deoxyribonucleic acid-platinum complexes and the subsequent deoxyribonucleic acid damage response [ 104 ].…”
Section: Applications Of Flavonoids In Sr In Reversing Drug-resistanc...mentioning
confidence: 99%
“…TLR4 activation led to an increase in the levels of HIF1α and VEGF, which were reversed by baicalein. Importantly, baicalein substantially reduced NF-κB phosphorylation in the tumor tissues of CRC-bearing xenograft mouse models [ 113 ].…”
Section: Animal Modelsmentioning
confidence: 99%
“…It also interfered with HIF-1α inhibition of mitochondrial biosynthesis. This increased the mitochondrial DNA content, restored the ROS, and thus increased the tamoxifen-induced mitochondrial apoptotic pathway [ 166 ].…”
Section: Signaling Molecules and Biological Pathways Targeted By Plan...mentioning
confidence: 99%